Kajian Ekologis Rafflesia Patma Blume di Cagar Alam Leuweung Sancang Jawa Barat - Dadang R Priatna; Ervizal A. M Zuhud; Hadi S Alikodra (Media Konservasi, 1989)
Rafflesia parma Blume is one of the 12 Rafflesia spp. found in Indonesia which has an attractive and relatively big flower and a unique life. As a holoparasite, this astonishing plant is particularly dependent on the distribution of, and its interaction with the liana host, Tetrasfigma sp.The distribution of R. patma is confined to the Leuweung Sancang Nature Reserve, the Pananjung Pangandaran Nature Reserve and the Nusa Kambangan Nature Reserve. The people in Java andKalimantan have been utilizing Rafflesia for traditional bio-medicine (such as for the raw material of jamu "patmosari") since a long time. However, illegal harvesting of the buds seem to ignore the sustained yield principle. Without any protection measures, this will lead to the extinction of the endemic plant species in the near future. The important components of R. patma habitat are described in this paper, among others are its association with the tropical rain forest, the characteris'ticsof the liana host, the pollinator and seed disperser and some aspects of the abiotic components.